Adherence to Madhhab as the Foundation of Religious Moderation Education: The Perspective of KH. M. Hasyim Asy’ari - Siti Mu'awanah; Khoirul Umam (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2024)
The discourse on religious moderation in contemporary Indonesia faces significant tension between the need to maintain social cohesion and the rise of polarization and exclusivist religious interpretations. This article analyzes the concept of madhhab adherence (bermadzhab) from the perspective of KH. M. Hasyim Asy’ari as an epistemological and pedagogical foundation for religious moderation education. Employing a qualitative approach with a historical-intellectual design, this study examines his major works, including Adab al-‘Ālim wa al-Muta‘allim, Risālah Ahl al-Sunnah wa al-Jamā‘ah, and Risālah fi Ta’akkud al-Akhdz bi Madzahib al-Arba‘ah, alongside relevant literature on pesantren traditions and Islamic moderation in Indonesia. The findings reveal that madhhab adherence in KH. M. Hasyim Asy’ari’s thought is not understood as passive imitation, but as a methodological commitment to scholarly authority, chains of transmission (sanad), and the discipline of usul al-fiqh. This framework safeguards the balance between theological orthodoxy and social inclusivity, while cultivating a religious character characterized by tawassuṭ (moderation), tawāzun (balance), and tasāmuḥ (tolerance). Within pesantren education, particularly in institutions affiliated with Nahdlatul Ulama, madhhab adherence is internalized through the study of classical Islamic texts (turāth), ethical formation (adab), and habituation in managing juristic differences (ikhtilaf) proportionally. The article concludes that madhhab adherence constitutes a robust epistemic framework for strengthening tradition-based religious moderation education. Moderation is thus not grounded in theological relativism or normative slogans, but in an educational process rooted in the pesantren’s intellectual tradition and historically validated scholarly authority.